Computer security and cryptography - Konheim, Alan G. (Wiley-Interscience, 2007)
Konheim (computer science, U. of Calif.-Santa Barbara) offers professionals and students in e-commerce and information technology the tools, techniques, and concepts needed to understand and implement data security systems. Coverage includes the history of cryptography, including the basic encryption systems and many of the cipher systems used in the 20th century; the theory of symmetric- and public-key cryptography; and a variety of cryptography applications. Included are chapters to develop technical details; chapters that describe a cryptosystem and possibly indicate method(s) of analysis; and chapters describing a cryptosystem, indicating method(s) of analysis, and providing problems to test the reader's understanding.